2017
DOI: 10.12968/jowc.2017.26.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' practice in preventing postoperative wound infections: an observational study

Abstract: Despite surgical wound care guideline recommendations on aseptic technique compliance, patient education, wound assessment and documentation practices, there is a clear gap between recommended and observed wound care practice. This study highlights an area where clinical practice is not reflective of evidence-based recommendations, suggesting that to minimise SSI as an adverse event, practice should be evaluated and strategies incorporating evidence into practice are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(99 citation statements)
references
References 37 publications
2
91
0
Order By: Relevance
“…Our findings illustrate a lack of adherence to principles and practices of aseptic technique that may indicate a knowledge deficit in this area. This is consistent with the results from our previous published observational study conducted in the same setting that found that over 14% nurse breached aseptic non‐touch technique, and 22% nurses did not use sterile gloves correctly during wound care (Ding et al, ). The term “asepsis” means free of potentially pathogenic microorganisms (Loveday et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings illustrate a lack of adherence to principles and practices of aseptic technique that may indicate a knowledge deficit in this area. This is consistent with the results from our previous published observational study conducted in the same setting that found that over 14% nurse breached aseptic non‐touch technique, and 22% nurses did not use sterile gloves correctly during wound care (Ding et al, ). The term “asepsis” means free of potentially pathogenic microorganisms (Loveday et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Understandably, clear and complete wound care documentation helps healthcare professionals to communicate and track patients’ wound healing process. Literature suggests that only 40%–75% of wound care episodes were documented (Gillespie, Chaboyer, Kang et al, ), with some of these being incomplete and some important information missing (Ding et al, ; Gillespie, Chaboyer, Kang et al, ; Wong, ). In our study, participants expressed their confusion about what form of documentation tool should be used (the EMR system in the form of programme notes vs. paper‐based WCP), and the types of information to document.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the low hand hygiene adherence rates (9.3% overall) following dressing change is a major departure from infection prevention recommendations, which is somewhat concerning. Findings from this study support the results of earlier research, suggesting incongruences in hand hygiene practices before and after patient care (Ding et al, ). Yet, in comparing practice variations across contexts, it is important to separate contextual factors that are outside the direct control at that level and those that are amenable to change (Sutherland & Levesque, ).…”
Section: Discussionsupporting
confidence: 90%
“…We modified an observational tool previously developed and rigorously tested in a pilot study (Ding, Lin, Marshall, & Gillespie, ) to audit contemporaneous wound management practices in the participating hospitals. Items in the audit tool included postoperative surgical wound management behaviours/activities used to prevent infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation